2006
DOI: 10.1080/07481180500348811
|View full text |Cite
|
Sign up to set email alerts
|

And Then the Dog Died

Abstract: Childhood grief and mourning of family and friends may have immediate and long-lasting consequences including depression, anxiety, social withdrawal, behavioral disturbances, and school underachievement. Childhood pet bereavement is no less important, because the pet is often considered a member of the family by the child. However, society does not always acknowledge the significance of pet bereavement, which can result in unresolved grief. This article, a case analysis with literature review, addresses childh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 86 publications
(91 reference statements)
1
41
0
Order By: Relevance
“…Whilst emotional responses to bereavement can be visceral, they are relational to wider external factors such as prior relationship with the deceased, whether the death was expected or not, and the bereaved person's social and cultural context (see Kaufman & Kaufman, 2006); they also relate to an individual's internal world view and baseline psychological state prior to bereavement and how they approach 'sense-making' of a death, which is central to the grieving process (Davies, 2002;Walter, 1996aWalter, , 1996b.…”
Section: Theorising Experiences Of Bereavement Grief and Mourningmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst emotional responses to bereavement can be visceral, they are relational to wider external factors such as prior relationship with the deceased, whether the death was expected or not, and the bereaved person's social and cultural context (see Kaufman & Kaufman, 2006); they also relate to an individual's internal world view and baseline psychological state prior to bereavement and how they approach 'sense-making' of a death, which is central to the grieving process (Davies, 2002;Walter, 1996aWalter, , 1996b.…”
Section: Theorising Experiences Of Bereavement Grief and Mourningmentioning
confidence: 99%
“…Here the focus is on human bereavement through death and consequent grief and mourning, but with an awareness of other forms of loss, such as the loss of home, nation, job or partner, and numerous embodied health-related losses such as mobility, fertility and sight. Grief and mourning may also occur as a result of cross-species bereavement between humans and pets, which can have profound effects on both parties (Kaufman & Kaufman, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A child can only understand as much as he or she has the capacity to at a certain developmental level. Limited personal experience can make the first loss in a child's life profound (Kaufman & Kaufman, 2006). For a child, moving for the first time may invoke a grief reaction similar to what may be experienced with the first death in a family.…”
Section: Cognitive Development and Griefmentioning
confidence: 99%
“…Helping them to understand and normalize their experiences is key to future mental health. Resolution of childhood grief, of any kind, is critical to adult psychological wellness (Field, 2006;Kaufman & Kaufman, 2006). Worden (2003) has suggested that there are tasks of mourning that one must complete.…”
Section: Grief Tasksmentioning
confidence: 99%
See 1 more Smart Citation